Performance analysis of interference-limited dual-hop amplify-and-forward two-way relaying systems. (2016) - Wen, Honghang; Ge, Jianhua
The performance of dual-hop amplify-and-forward (AF) two-way relaying systems with multiple co-channel interferers at the AF relay and two noisy end-sources is investigated in this paper. For such, a tight closed-form approximation is derived for the outage probability and average symbol error probability of the considered systems. In particular, in high SIR regions, with an increasing system SIR, the outage and average error performance does not vary with the number of interferers once the total interference power is given. Monte Carlo simulation results are presented to corroborate the proposed theoretical analysis.